Experiences of Patients With Diabetes Attending a Publicly Funded Eye Care Pathway in Western Sydney: A Qualitative Study. (October 2021) - Ford, Belinda K; Angell, Blake; White, Andrew JR; Duong, Annita; Hiidome, Saya; Keay, Lisa
Diabetic retinopathy (DR) complications can be prevented with regular screening and timely access to an ophthalmologist for treatment. But there are patient and health system barriers that can impact access to DR services. This study aims to identify enablers and barriers for accessing public DR eye care services in a low socio-economic urban area of Australia. We conducted a qualitative study using semi-structured interviews for patients with diabetes aged 35 years and older attending public ophthalmology services. Interviews were analyzed to identify themes and subthemes; and the COM-B framework was used to interpret the complex behavioral mechanisms, including capability, opportunity, and motivation factors, to explain adherence to DR eye care. Three main themes and 7 sub-themes relating to patient experiences of DR care were derived. Patients were found to be passive actors in their DR eye care, but patients trusted clinicians and were determined to maintain their vision and quality of life. The barriers and facilitators of care related to the health system (service availability and recall–reminder systems) and patient experiences (choices, knowledge, and fear). The findings of this study will guide patient-centered initiatives to target and improve access to DR care. Strategies should focus on improving communication between eye care providers, and communication with patients to empower them to become more active players in healthcare decisions.